Anesthesia Considerations for Cesarean Delivery in a Patient with Loeys-Dietz Syndrome. (15th February 2015) - Cronin, Jessica; Cuschieri, Heidi Bazick; Dong, Xiaobo; Oswald, Gretchen; Russo, Melissa; Dietz, Hal; Murphy, Jamie
Abstract : A 28-year-old primigravida female with Loeys-Dietz syndrome presented at 36 weeks' gestation for scheduled primary elective cesarean delivery. The patient had clinical findings consistent with this diagnosis, including mild aortic root dilation, chronic right vertebral artery dissection with 2 intracerebral aneurysms, and small ectasias of the thecal sac in the lumbar region. Pregnant patients with Loeys-Dietz syndrome have significant risks, including aneurysm rupture, new aneurysm formation, and uterine rupture. After a thorough preoperative evaluation, the patient underwent successful general anesthesia focused on maintenance of intraoperative hemodynamic stability and minimal intraoperative blood loss.